ESPECTRO POLÃNICO DE AMOSTRAS DE MEL DE ð˜ˆð˜±ð˜ªð˜´ ð˜®ð˜¦ð˜ð˜ð˜ªð˜§ð˜¦ð˜³ð˜¢ L. PROVENIENTES DE NOVA SOURE, BAHIA - Almeida, Alberto Magno Matos de; Carvalho, Carlos Alfredo Lopes de; Abreu, Ricardo Duarte; Santos, Francisco Assis Ribeiro dos; AraÃºjo, Rita de CÃ¡ssia Matos dos Santos; Oliveira, Paulino Pereira (REVISTA DE AGRICULTURA, 2020)
ESPECTRO POLÃNICO DE AMOSTRAS DE MEL DE ð˜ˆð˜±ð˜ªð˜´ ð˜®ð˜¦ð˜ð˜ð˜ªð˜§ð˜¦ð˜³ð˜¢ L. PROVENIENTES DE NOVAÂ SOURE, BAHIA